Balancing Student Mobility Rights and National Higher Education Autonomy in the European Union. - Hoogenboom, Alexander (Nijhoff Studies in European Union Law Ser., 2017)
Traditionally viewed as a positive phenomenon, student mobility has recently come under critical scrutiny as a result of the financial crisis pushing European solidarity to its breaking point, and the fear of excessive EU incursion into the autonomy of Member States with respect to their higher education systems. In Balancing Student Mobility Rights and National Higher Education Autonomy in the European Union , Alexander Hoogenboom contributes to the ongoing and evolving debate from a legal perspective. The book offers recommendations with a view to reconcile the mobility rights of Union citizens for study purposes and the need to respect Member State autonomy in the organisation of their higher education systems. The argument made suggests rethinking established principles in EU free movement law while encouraging greater EU involvement in student funding opportunities.